Synthesis of Li2Ni2(MoO4)3 as a high-performance positive electrode for asymmetric supercapacitors. Issue 22 (27th February 2017) - Du, Dongwei; Lan, Rong; Xie, Kui; Wang, Huanting; Tao, Shanwen
Abstract : A NASICON-type compound, Li2 Ni2 (MoO4 )3 was successfully synthesized via a combustion method to be used as positive electrode for asymmetric supercapacitors with good performance. Abstract : A NASICON-type compound, Li2 Ni2 (MoO4 )3 was successfully synthesized via a combustion method. The as-synthesized Li2 Ni2 (MoO4 )3 is fiber-like grains with an average length of 1–2 μm. As an electrode for pseudocapacitors, in 2 M LiOH, its specific capacitance reached 1137 F g −1 and 717 F g −1 at current density of 1 A g −1 and 20 A g −1 respectively, exhibiting 63% capacity retention. Moreover, in asymmetric supercapacitors with an activated carbon electrode as the negative electrode, the energy density of 36.5 W h kg −1 was obtained at the average power density of 420 W kg −1 . The fabricated asymmetric supercapacitor also exhibited good electrochemical stability, specifically, the specific capacitance was retained at 68% of the initial value even after 10 000 cycles at 2 A g −1 . These observations suggest that the prepared Li2 Ni2 (MoO4 )3 is a prospective candidate for high-performance supercapacitors.